Observation of Electron Cloud Instabilities and Emittance Dilution at the Cornell Electron-Positron Storage Ring Test Accelerator. (11th April 2016) - Holtzapple, R.L.; Billing, M.G.; Campbell, R.C.; Dugan, G.F.; Flanagan, J.; McArdle, K.E.; Miller, M.I.; Palmer, M.A.; Ramirez, G.A.; Sonnad, K.G.; Totten, M.M.; Tucker, S.L.; et al.
Abstract: Electron cloud related emittance dilution and instabilities of bunch trains limit the performance of high intensity circular colliders. One of the key goals of the Cornell electron-positron storage ring Test Accelerator (CesrTA) research program is to improve our understanding of how the electron cloud alters the dynamics of bunches within the train. Single bunch beam diagnotics have been developed to measure the beam spectra, vertical beam size, two important dynamical effects of beams interacting with the electron cloud, for bunch trains on a turn-by-turn basis. Experiments have been performed at CesrTA to probe the interaction of the electron cloud with stored positron bunch trains. The purpose of these experiments was to characterize the dependence of beam-electron cloud interactions on the machine parameters such as bunch spacing, vertical chromaticity, and bunch current. The beam dynamics of the stored beam, in the presence of the electron cloud, was quantified using: 1) a gated beam position monitor (BPM) and spectrum analyzer to measure the bunch-by-bunch frequency spectrum of the bunch trains; 2) an x-ray beam size monitor to record the bunch-by-bunch, turn-by-turn vertical size of each bunch within the trains. In this paper we report on the observations from these experiments and analyze the effects of the electron cloud on the stability of bunches in a train under many different operational conditions.